Solving the expression [tex]\frac{1}{3}-(-4+\frac{3}{5})[/tex] we get [tex]\frac{56}{15}[/tex]
Step-by-step explanation:
Solve the expression: [tex]\frac{1}{3}-(-4+\frac{3}{5})[/tex]
First we will solve the terms inside the round brackets
[tex]\frac{1}{3}-(-4+\frac{3}{5})\\Taking\,\,LCM\,\,of\,\,1\,\,and\,\,5\,\,i.e\,\,5\\=\frac{1}{3}-(\frac{-4*5+3}{5})\\=\frac{1}{3}-(\frac{-20+3}{5})\\=\frac{1}{3}-(\frac{-17}{5})\\[/tex]
Now opening the bracket (-)(-)=+
[tex]=\frac{1}{3}+\frac{17}{5}\\Taking\,\,LCM\,\,of\,\,5\,\,and\,\,i.e\,\,15\\=\frac{1*5+17*3}{15}\\=\frac{5+51}{15}\\=\frac{56}{15}[/tex]
So, solving the expression [tex]\frac{1}{3}-(-4+\frac{3}{5})[/tex] we get [tex]\frac{56}{15}[/tex]
Keywords: Solving Fractions
Learn more about Solving Fractions at:
#learnwithBrainly